"I feel like marijuana is the only drug that wouldn't kill me": perceptions of cannabis use in previously incarcerated Black men who have sex with other men - Rey Flores; Jared Kerman; John Schneider; Nina Harawa (BMC, 2023)
Abstract Background Fragmented state laws have impacted cannabis uptake and perceptions in the USA. Little research has explored the attitudes, beliefs, and social network influences of young Black men who have sex with men (BMSM) who have experienced incarceration and use cannabis. While problematic cannabis use is not well defined and understudied, scholars have found that a person's social network can mediate problematic substance use and reduce recidivism rates by providing both tangible and emotional support. This analysis examines how social networks contribute to cannabis perceptions and use among BMSM with criminal legal system involvement in Chicago, IL, and Houston TX. Methods Researchers conducted interviews with 25 cis gender Black men informed by life course theory, with a focus on the role of social networks, incarceration, and other life experiences in substance use. All interviews were audio-recorded, de-identified, and transcribed; participants were compensated $50. A deductive-inductive thematic analysis was used to analyze all qualitative data collected. Results Twelve BMSM in Chicago and 13 BMSM in Houston (M = 26.6 years old, SD = 3.7) were interviewed. A majority identified as gay (56%), with 12 participants (48%) reporting having a high school diploma or equivalent; their average age of first substance use was 15.2 (SD = 2.9). Participants perceived cannabis usage to be categorically distinct from other intoxicating substance usage, with many describing it as not harmful and potentially beneficial. Three themes shaped their choices and attitudes regarding cannabis and "hard" drugs-social networks, need fulfillment, and knowledge of risk. Conclusion Participant descriptions of cannabis use emphasize their drug-use behavior as being produced by agent decision-making and risk assessment. Future work should expand on how these decisions are made, and how social networks can be leveraged to encourage non-harmful drug consumption behaviors.